PENGARUH MOTIVASI BERPRESTASI DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI PDAM TIRTANADI PROVINSI SUMATERA UTARA CABANG MEDAN KOTA - Siregar, Baharuddin; Irawani S, Nurmaida (Universitas Medan Area, 2010)
This study aims to see the influence of achievement motivation and discipline to the performance of employees working Tirtanadi PDAM Medan, North Sumatra branch of the City. In line with the theoretical basis of existing, proposed hypotheses achievementÂ motivation significantly influence employee performance Tirtanadi PDAM Medan, North Sumatra branch of the City.In proving the above hypothesis, we used data analysis method Multiple Regression. Based on data analysis of the results obtained Â there is significant influence between achievement motivation and labor discipline on the performance of employees. This is evidenced by the coefficient Freg = 5.701 where p <0.050. 2) As for the contribution of achievement motivation variables on the performance of employees in the civil branch of Medan City PDAM Tirtanadi with 17.72% contribution. Meanwhile variables affect labor discipline or have a role on the performance of employees by 18.92%. The total effective contribution of these two independent variables (achievement motivation and discipline of work) on the performance of employees amounted to 20.20%. In general, the results of this study illustrate that stated that the subject of this study have very high achievement motivation and disciplined work is very high.